2008
DOI: 10.1002/ange.200803116
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereospecific Generation of Helical Chirality by Imprinting with Amino Acids: A Universal Sensor for Amino Acid Enantiopurity

Abstract: Helizität kann einem 2,2′‐Dihydroxybenzophenon‐Derivat hoch stereospezifisch übertragen werden (siehe Bild). Eine einzige Aminosäure bindet an den Rezeptor, sodass ein Imin mit zwei internen Wasserstoffbrücken entsteht. Dank der Azogruppen lässt sich die Enantiomerenreinheit der Aminosäure CD‐spektroskopisch bestimmen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[6][7][8][9][10] Gawronski and colleagues 11,12 and others exploited essentially the same concept for chirality chemosensing by using molecular bevel gears, propellers, 13 or other probes that can afford a CD-active helical arrangement. 14,15 Similarly, Berova and Nakanishi, [16][17][18][19] Anslyn, [20][21][22][23] Canary, 24,25 Borhan, 26,27 and many others have developed a variety of intriguing stereodynamic chemosensors that generate strong CD signals in the presence of a chiral bias. [28][29][30] In many cases, the CD output of the chemosensor allows determination of the absolute configuration and the enantiomeric composition of the chiral analyte.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Gawronski and colleagues 11,12 and others exploited essentially the same concept for chirality chemosensing by using molecular bevel gears, propellers, 13 or other probes that can afford a CD-active helical arrangement. 14,15 Similarly, Berova and Nakanishi, [16][17][18][19] Anslyn, [20][21][22][23] Canary, 24,25 Borhan, 26,27 and many others have developed a variety of intriguing stereodynamic chemosensors that generate strong CD signals in the presence of a chiral bias. [28][29][30] In many cases, the CD output of the chemosensor allows determination of the absolute configuration and the enantiomeric composition of the chiral analyte.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The development of conformationally flexible receptors capable of reporting a molecular recognition event upon binding to a substrate provides new avenues for chiroptical analysis. [5][6][7][8][9][10] For example, Rosini and Toniolo demonstrated that the absolute configuration of chiral amino acids, carboxylic acids, and alcohols can be correlated to the ICD output of a covalently linked stereodynamic biphenyl reporter unit. [11][12][13][14][15][16] The same principles have been exploited with molecular bevel gears, 17 propellers, 18 and other well-defined arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] The same principles have been exploited with molecular bevel gears, 17 propellers, 18 and other well-defined arrangements. 9,19,20 Berova, Nakanishi, Anslyn, Canary, and others have introduced elegant probes showing distinct chiral amplification and ICD signals that can be used for both reliable structural analysis and enantiomeric excess (ee) determination of chiral substrates. 7,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Because of the ever-increasing demand for enantiopure pharmaceuticals, the development of fast, accurate, and practical methods for the stereochemical analysis of amino alcohols, which serve as chiral building blocks of many bioactive compounds, has become very important.…”
Section: Introductionmentioning
confidence: 99%
“…The chiral amplification process and sensing response can then be exploited for qualitative and quantitative stereochemical analysis of the bound substrate. [16][17][18][19][20] Seminal progress with the development of a variety of chiroptical chemosensors and powerful chirality sensing assays that can be used for the determination of the absolute configuration and enantiomeric excess (ee) of many compounds has been made by Berova and Nakanishi, [21][22][23][24] Anslyn, [25][26][27][28][29] Canary, 30, 31 Joyce, 32 and Borhan. The covalent attachment of a chiral amino acid, carboxylic acid, amine, or alcohol was found to effectively disturb the racemic equilibrium of the biphenyl conformations in the probe, thus inducing spontaneous chirality amplification.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Several probe designs with interesting CD reporter units including molecular bevel gears 13,14 and propellers, 15 have been introduced by Gawronski, Katoono, and others. [16][17][18][19][20] Seminal progress with the development of a variety of chiroptical chemosensors and powerful chirality sensing assays that can be used for the determination of the absolute configuration and enantiomeric excess (ee) of many compounds has been made by Berova and Nakanishi, [21][22][23][24] Anslyn, [25][26][27][28][29] Canary, 30,31 Joyce, 32 and Borhan. [33][34][35] To this end, our group has introduced axially chiral salicylaldehydederived receptors that undergo fast substrate binding and subsequent asymmetric transformation of the first kind toward a highly CD-active conformation.…”
mentioning
confidence: 99%